Confirmación de la presencia de la serpiente de cascabel Crotalus scutulatus para el Estado de México, México - Fernández-Badillo, Leonardo; Morales- Capellán, Nallely; Contreras-Patiño, Rafael; Carreño-Cervantes, Angelica (Instituto de Ecología, A.C., 2016)
We present a new record of rattlesnake Crotalus scutulatus collected in the county of La Paz, Mexico, that confirms the presence of the species for the Mexican state of Mexico. There is a dubious prior record of a specimen collected on 1967. Either way this species has not been collected again until now.